The Impact Of Covid-19 On Digital Sharia Banking In Padangsidimpuan City - Muhammad Wandisyah R Hutagalung; Darwis Harahap; Muhammad Isa (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2022)
The high level of direct transactions at Islamic banks during the Covid-19 pandemic is a common sight in Padangsidimpuan City. In fact, in the current 4.0 era, Islamic banks have provided various digital-based services to make it easier for customers to transact without having to come to Islamic banks, especially during the pandemic. This study aims to see the impact of the Covid-19 pandemic on the use of Digital Syariah Banking in Padangsidimpuan City. This study uses descriptive qualitative data analysis techniques with 400 samples. This study resulted that Covid-19 had no impact on the use of Digital Syariah Banking in Padangsidimpuan City. This is due to three factors, namely the public's view of Covid-19, security, and the location of Islamic banks.